Systematic determination and diagnostic characters of Ranikothalia nuttalli in the late Paleocene–early Eocene deposits in Padagi stratigraphic section, Sefid-Abeh Basin, Sistan Suture Zone - Mohammadnabi Gorgij; Somayyeh Shahraki Mirzaei (Journal of Stratigraphy and Sedimentology Researches, 2023)
Of the most important characteristics of the Ranikothalia genus, as large benthic foraminifera, are the existence of ornamentation in the external part of the shell especially around the central umbilicus knob, marginal mesh channels (MMC) in the marginal chord, trabeculate system with channels, V-shape plate in the floor of chambers and accumulation of septum that differentiated this genus from Nummulites genus and placing it in the Palaeonummulitinae sub-family. The Ilerdian transgression near the P5 Zone (Pelagic P5) is a stratal key surface for the determination of the Paleocene-Eocene boundary in the neritic deposits. Ranikothalia nuttalli as an index species is used for recognition of the Paleocene–Eocene boundary in the Neo-Tethys shallow water successions. This species, in the Padagi section, resembling the Pakistan Indus Basin, accompanied with Miscellanea miscella, Discocyclina sp., Discocyclina sp., Assilina sp. that indicated SBZ5/6 and suggested lower Ilerdian (earliest Eocene) age. Keywords: Ranikothalia , Ilerdian, systematic, Sistan Suture Zone